They Called Them Soldier Boys : A Texas Infantry Regiment in World War I - Ball, Gregory W. (Book collections on Project MUSE., 2013)
They Called Them Soldier Boys offers an in-depth study of soldiers of the Texas National Guard's Seventh Texas Infantry Regiment in World War I, through their recruitment, training, journey to France, combat, and their return home. Gregory W. Ball focuses on the fourteen counties in North, Northwest, and West Texas where officers recruited the regiment's soldiers in the summer of 1917, and how those counties compared with the rest of the state in terms of political, social, and economic attitudes. Through the use of Selective Service Registration cards, a sample of 1,096 members of the regimen.